The Effect of some discontinuities on rock Slope Failure in Some Selected Sites in Bammo Anticline - Hameed, Aya Ali; Alkubaisi, Manal Shakir (Iraqi Journal of Science, 2019)
Field studies of the slopes of Bammo anticline, in Northeast of Iraq, was carried out in five selects stations, where rock slopes and the discontinuities were surveyed in these stations and its relationships with failures were determined. The field work was revealed the abundance of rock slope failures, the dominant types are rock fall and toppling. Slope stability assessment was carried out by stereographic projection was made using software (GEOrient 9.5.0), the slopes were classified according to (Al-Saadi, 1981), and the rocks were described in engineering terms according to (Anon, 1972) depending on field data. The study also revealed that the factors affecting slope stability in the study area were slope angle, height, dip of strata, and discontinuities. Some remedial measures are suggested for the unstable slopes, and the most important removal of the detached block.